The Double Role Model of National Police in Handling Conflict - Suparmin Suparmin (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
It is undeniably that the National Police has mandate to create a harmonious and peace social atmosphere. Moreover Indonesia is multicultural country: ethnic, language, religion, and culture. It sometimes becomes a trigger of communal conflicts. Having this a vital role, the National Police tries to maximize its role to prevent the grass-root conflict and more importantly to maintain the national stability. This study is basically aimed to analyze the National Police’s important role in resolving the conflict especially, political conflict between supporters of political parties. Recently, this conflict has caused serious problems either politically, socially and even economically. By using the double role model, the National Police will in turn be able to resolve all kinds of conflict in peace and harmony.   Keywords: conflict, role model, national police, harmony